Preventing Cardiomyopathy in DMD: A Randomized Placebo-Controlled Drug Trial. Issue 5 (October 2021) - Bourke, John P.; Watson, Gillian; Spinty, Stefan; Bryant, Andrew; Roper, Helen; Chadwick, Thomas; Wood, Ruth; McColl, Elaine; Bushby, Kate; Muntoni, Francesco; Guglieri, Michela
Abstract : Objective: To determine whether a combination of 2 heart medications would be tolerated and could prevent/delay the onset of cardiomyopathy in boys with Duchenne muscular dystrophy (DMD) compared with placebo. Methods: This multicenter, parallel group, 1:1 patient randomized, placebo-controlled study of prophylactic perindopril and bisoprolol recruited boys with DMD aged 5–13 years, with normal ventricular function. Repeat assessments of left ventricular (LV) function, electrocardiogram, and adverse event reporting were performed 6 monthly. The primary outcome was change in ejection fraction between arms after 36 months. The study was approved by the National Research Ethics Service Committee East Midlands—Derby. Results: Eighty-five boys were recruited (76% on steroid therapy) and randomized to combination heart drugs or matched placebo. Group change in left ventricular ejection fraction (LVEF%) at 36 months from baseline was −2.2% ± 6.0% and −2.9% ± 6.1% in active and placebo arms (adjusted mean difference: −2.1, 95% CI −5.2 to 1.1). There was no difference between treatment arms over repeated assessments (analysis of variance) up to 36 months (trial arms p = 0.53); arm-over-time ( p = 0.44). Four participants on placebo but none on active therapy were withdrawn due to deteriorations in LV function. Secondary outcomes did not differ between arms either. Thirty-six serious adverse events occurred none due to cardiac events or trial medication. Conclusions: Combination therapy was well tolerated. Consistent with the previous prophylactic perindopril heart study, there was no evidence of group benefit after 36-month treatment. Classification of Evidence: This study provides Class I evidence that combination perindopril-bisoprolol therapy was well tolerated but did not change decline in LVEF significantly in boys with DMD.